2006
DOI: 10.1136/jnnp.2006.106054
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of single-photon emission computed tomography in differentiating frontotemporal dementia from Alzheimer's disease

Abstract: Background: Alzheimer's disease (AD) and frontotemporal dementia (FTD) are the commonest causes of presenile dementia. In the absence of a biological marker, diagnosis is reliant on clinical evaluation. Confirmation is often sought from neuroimaging, including single-photon emission computed tomography (SPECT). Most previous SPECT studies lack pathological validation. Aim: To examine the accuracy of SPECT in differentiating FTD from AD in patients with subsequent pathological confirmation. Methods: Technetium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 30 publications
8
58
0
2
Order By: Relevance
“…Thus, it is difficult to sharply distinguish between PDD and AD using neuropsychological tests, particularly at the early stages [2]. Mild PDD is often misdiagnosed and is commonly confused with mild AD [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is difficult to sharply distinguish between PDD and AD using neuropsychological tests, particularly at the early stages [2]. Mild PDD is often misdiagnosed and is commonly confused with mild AD [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Patterns of frontal or anterior temporal hypoperfusion with preserved parietal signal on SPECT can distinguish FTD from AD with a sensitivity and specificity of approximately 80%. 13 Similar patterns of hypometabolism on FDG-PET imaging show approximately 90% diagnostic accuracy when distinguishing FTD from AD. 14 PET amyloid imaging shows a similarly high accuracy of…”
Section: Neuroimaging Characteristicsmentioning
confidence: 95%
“…Recently, published guidelines have suggested that SPECT can be used to differentiate between AD, VaD, FTD, and DLB in cases where diagnostic uncertainty exists [27,28]. Individual studies evaluating the diagnostic utility of SPECT imaging, however, have differed in terms of sample size, patient characteristics, clinical diagnostic criteria employed, cognitive testing, and imaging acquisition [17,29]. Studies to date have also focused on the diagnostic utility of SPECT in older adults with AD compared, predominantly, to cognitively unimpaired controls [30].…”
Section: Discussionmentioning
confidence: 99%